Accelerating image acquisition in 64-MDCT: The influence of scan parameters on image resolution and quality in a phantom study - Klink, Thorsten; Regier, Marc; van Stevendaal, Udo; Grass, Michael; Adam, Gerhard; Begemann, Philipp (Clinical Imaging, 2012)
Computed tomographic (CT) image resolution and quality were evaluated utilizing varying scan protocols with accelerated image acquisition.A resolution phantom with hole diameters from 0.2 to 1.0 mm was scanned in axial, coronal, and sagittal plane using a 64-slice multidetector CT with varying scan parameters.No relevant differences in image resolution and quality were detected between the fastest scan protocol, with the shortest rotation time and highest pitch, and the slowest protocol.Accelerated CT protocols resulted in diagnostic images with adequate resolution and quality. © 2012 Elsevier Inc.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Artifacts; Computed tomography; Image quality; Phantom; Resolution